FIRST EXPERIENCE IN USING SATELLITE DATA FOR MONITORING THE HYDRO-FLUID REGIME OF LOKBATAN VOLCANO IN THE ASSESSMENT OF SEISMIC EVENT RISKS IN THE REGION - HUSEYNOV, Arif; NESTEROVSKYI, Viktor; HUSEYNOVA, Ayten (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Mud volcanoes are unique natural structures affecting the environment by continuous emissions of gas-liquid fluids, mud breccia and mudflows. Despite extensive research and a substantial dataset on mud volcanism, the understanding of the fluid dynamics and hydrogeological processes associated with these systems remains a subject of ongoing debate. Globally, there are more than 2,500 mud volcanoes distributed across 42 countries (Aliyev et al., 2015), highlighting their widespread occurrence. Azerbaijan represents a unique region for the study of contemporary mud volcanism, hosting more than 350 mud volcanoes within a relatively small territory. Among them, the Lokbatan mud volcano is the most active, with 28 recorded eruptions. In this context, a comprehensive approach to studying the activity of mud volcanoes, including satellite monitoring, is highly relevant. Methods. The study employed remote sensing techniques to analyze the hydro-fluid regime of the Lokbatan mud volcano. Specifically, satellite imagery was used to calculate a moisture index for the volcano field. For the first time, this index was remotely measured, enabling assessment of surface moisture dynamics as a proxy for fluid migration and subsurface activity. Results. The satellite-derived moisture index showed clear correlations with mud volcanic activity. Observations indicate that variations in the moisture index correspond to shifts in the fluid regime of the volcano, reflecting possible underground fluid migration or pressure changes prior to eruptions. Conclusions. The study demonstrates the potential of satellite-based monitoring in assessing the hydro-fluid regime of active mud volcanoes. The approach provides an effective, low-cost alternative to field-based observations and can support early warning systems for seismic or eruptive events. These findings contribute to the development of preventive strategies for managing geological hazards in seismically active regions.
Keywords: Mud volcano; satellite images; fluids; NDWI; monitoring